2003
DOI: 10.1128/iai.71.4.2208-2217.2003
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegansas a Model Host forStaphylococcus aureusPathogenesis

Abstract: Staphylococcus aureus, an important pathogen of humans and other warm-blooded animals, is also capable of killing the nematode Caenorhabditis elegans. Here, we show that C. elegans organisms that are fed S. aureus die over the course of several days in a process that is correlated with the accumulation of bacteria within the nematode digestive tract. Several S. aureus virulence determinants known or speculated to be important in mammalian pathogenesis, including the quorum-sensing global virulence regulatory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
341
0
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 304 publications
(366 citation statements)
references
References 76 publications
14
341
0
11
Order By: Relevance
“…In contrast, relatively little is known about innate immunity in the nematode Caenorhabditis elegans. Recent work has shown that C. elegans is killed by a variety of bacterial and fungal pathogens, including Pseudomonas aeruginosa (4)(5)(6)(7)(8)(9)(10)(11)(12). When this experimental host-pathogen system was used, a forward genetic screen for C. elegans mutants exhibiting enhanced susceptibility to P. aeruginosa-mediated killing (Esp phenotype) identified two components of a mitogen-activated protein kinase (MAPK) signaling cascade, the MAPK kinase kinase, NSY-1, and the MAPK kinase, SEK-1, that are required for pathogen resistance (13).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, relatively little is known about innate immunity in the nematode Caenorhabditis elegans. Recent work has shown that C. elegans is killed by a variety of bacterial and fungal pathogens, including Pseudomonas aeruginosa (4)(5)(6)(7)(8)(9)(10)(11)(12). When this experimental host-pathogen system was used, a forward genetic screen for C. elegans mutants exhibiting enhanced susceptibility to P. aeruginosa-mediated killing (Esp phenotype) identified two components of a mitogen-activated protein kinase (MAPK) signaling cascade, the MAPK kinase kinase, NSY-1, and the MAPK kinase, SEK-1, that are required for pathogen resistance (13).…”
mentioning
confidence: 99%
“…When this experimental host-pathogen system was used, a forward genetic screen for C. elegans mutants exhibiting enhanced susceptibility to P. aeruginosa-mediated killing (Esp phenotype) identified two components of a mitogen-activated protein kinase (MAPK) signaling cascade, the MAPK kinase kinase, NSY-1, and the MAPK kinase, SEK-1, that are required for pathogen resistance (13). RNA interference (RNAi) inactivation of pmk-1, the gene encoding the p38 MAPK that functions downstream of NSY-1 and SEK-1, also resulted in enhanced susceptibility to killing by bacterial pathogens (11,13), and immunoblot analysis showed diminished activation of PMK-1 in nsy-1 and sek-1 mutants. Furthermore, pathogen-elicited apoptosis in C. elegans depended on PMK-1 signaling (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although mouse models have been used for these purposes, simpler invertebrates such as Caenorhabditis elegans have recently become more attractive for assessing the in vivo biological costs of antibiotic resistance (23,24). Many bacterial genes known to be required for mammalian pathogenesis are needed also in the nematode (1,9,11,15,16,27,28). Some bacterial pathogens, such as Salmonella enterica serovar Typhimurium are able to establish a persistent infection in the intestine of C. elegans, reducing the life span of the host.…”
mentioning
confidence: 99%
“…C. elegans has also been reported as a successful model for the investigation of virulence-associated factors of human pathogens such as Burkholderia pseudomallei 10) , Cryptococcus neoformans 19) , Enterococcus faecalis 27) , enteropathogenic Escherichia coli 2,16) , Listeria monocytogenes 34) , P. aeruginosa 32) , Serratia marcescens 14) , Shigella flexneri 6) , Staphylococcus aureus 11,28) , and Vibrio vulnificus 9) .…”
Section: Introductionmentioning
confidence: 99%